無線智慧聯網通訊系統之前瞻技術研究-子計畫一：高效率自我組織無線網狀機器對機器網路之研究 - 陳耀宗; CHEN YAW-CHUNG (My University, 2012)
機器對機器(Machine-to-Machine, M2M)通訊技術或稱智慧聯網或物聯網(Internet of Things, IOT)，在不需人為介入的情況下，讓各種偵測裝置或智慧機器能隨時隨地獲取與共享不同環境下的資訊，並透過電信網路或網際網路傳輸至後端伺服器進行運算處理，或彼此分享資訊，以幫助人類達到對生活周遭資訊的掌握、分析及控制。其應用涵蓋健康照護、智能家庭、環境監測、產業自動化、物品管理、災害防治、及追蹤監控等。 然而新興的機器對機器通訊仍然面對許多技術上的挑戰，例如如何設置與佈建符合網路通訊主要特性與需求的機器對機器架構。機器對機器通訊主要特性與需求包含：低成本佈建、自我組織、大量裝置、大量裝置傳輸、高可靠度、進階的存取優先權、低能源消耗、低行動性、安全性、低延遲性、群體控制等。為了支援機器對機器通訊，多項延伸標準也正在制定中，包含3GPP、IEEE802.16p (WiMAX)、802.11(WiFi)、802.15.4 (Zigbee)等。但標準的制定耗時，因此如何透過現有技術設計一套滿足機器對機器通訊主要特性與需求的架構在目前來看是較為可行的方法。 本計畫之目標，是透過網際網路、無線網狀網路(Wireless Mesh Network)、IPv4/IPv6 雙協定、P2P技術、與行動管理技術，研究設計一套架構以有效支援機器對機器之通訊。根據研究文獻，自我組織、大量裝置之資料傳輸、高可靠度、進階的存取優先權、低能源消耗、低行動性、安全性、低延遲性、群體控制等需求與特性皆可透過一套完善的網路進入/重新進入(Network Entry/Re-entry)程序達成，因此本計畫第一步即為設計一套有效的網路進入/重新進入機制，來管理整個機器對機器通訊裝置，此機制亦能使得某個裝置能快速有效的搜尋到其它裝置，以取得其他裝置的資訊，而由於機器對機器通訊的其中一項特性是大量的裝置充斥於網路中，因此設計時必須考慮分散式的管理機制，此網路進入/重新進入機制的設計可透過分散搜尋與研究目前無線網狀網路的相關程序來修改為適用於機器對機器通訊。計畫的第二步則著眼於設計一有效的群體控制機制，由於將機器對機器通訊內的裝置有效的分群之後，不僅能透過要求同一群內的裝置一起偵測重複相同的資料，達到高可靠性；亦可透過要求同一涵蓋範圍內的多個裝置協調並選擇某一裝置負責監測資料，達到其他裝置節能的功效。計畫的第三步則著眼於應用在智能交通運輸管理的移動性裝置，系統必須能快速的定位移動裝置的位置，且當必要時，此裝置能透過一套機制與其它裝置互相通訊，以取得位置相關資訊。最後本計畫為一子計畫，所提出來的機制必須跟總計畫和其他子計畫互相合作，所以一直會與其它子計畫互動搭配以解決實際問題。

Machine-to-Machine (M2M) communications, also called Internet of Things (IOT), is characterized by involving a large number of intelligent devices sharing information and making collaborative decisions without direct human intervention. The M2M use cases include healthcare, smart home, environmental monitoring, industrial automation, material/merchandise management, disaster prevention, object tracking and monitoring etc. M2M communications is the most promising solution for the future intelligent applications. However, M2M communications still faces many technical challenges, for example, how to design an M2M architecture that satisfies the requirements of M2M communications. The requirements and characteristics of M2M communications such as low cost deployment, self-organization, massive devices, massive device transmission, high reliability, enhanced access priority, extremely low power consumption, low mobility, security, low latency, and group control. On the other hand, many standards including 3GPP, IEEE 802.16p (WiMAX), 802.11(WiFi), and 802.15.4 (Zigbee) are moving quickly to support M2M communications. However, it needs quite a bit of time to define these standards. Hence, it is a promising solution that is to design the M2M architecture through the nowadays available technologies. We will design an architecture that supports the M2M communications based on the advanced technologies including wireless mesh network, IPv4/IPv6 dual stack, MP2P, and mobility management. According to the literature, most of the requirements for M2M communications can be achieved by an optimized network entry/re-entry procedure. Therefore, the first step of the project is to investigate and design an efficient network entry/re-entry procedure to manage the M2M devices. After developing the efficient network entry/re-entry procedure, the devices in the network can find and identify each other quickly. The second step of the project is to develop a group control mechanism that can achieve the goals of energy saving and high reliability, because a requested task can be performed either by single group member or by multiple group members. The third step focuses on the mobile devices which are deployed on intelligent traffic/transportation management, so that the mobile devices can be quickly located. The final step of the project is to integrate with other projects and to achieve a practical technical advances or breakthrough.
Efficient Self-Organization Mesh Network for Wireless Machine-To-Machine Communications
Keywords: 機器對機器通訊; IPv4/IPv6; P2P; 無線網狀網路; 智慧聯網; 物聯網; Machine-to-Machine Communication; IPv4/IPv6; MP2P; Wireless Mesh Network; Internet of Things